2014
DOI: 10.1186/1999-3110-55-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foliar application of salicylic acid and nitric oxide in alleviating iron deficiency induced chlorosis of Arachis hypogaea L.

Abstract: BackgroundThe aim of this experiment was to analyze the alleviation mechanism of exogenous salicylic acid (SA) and sodium nitroprusside (SNP, a nitric oxide donor) on peanut seedlings under Fe deficiency. The effects of SA and SNP on iron uptake and availability, ions balance and oxidant damage were studied with foliar application of exogenous 1.0 mM SA (SA) or 2.5 mM SNP (SNP) or 0.5 mM SA+1.25 mM SNP [1/2(SA+SNP)] or 1.0 mM SA+2.5 mM SNP (SA+SNP).ResultsThe results showed that after 21 days treatment, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 55 publications
9
54
0
Order By: Relevance
“…The highest iron content was found in SA-treated plants. Increased Fe concentration resulting from SA application was also reported in Arachis hypogaea [Kong et al, 2014]. The lowest Fe level was detected in the leaves of plants watered with CaCl 2 .…”
Section: Resultsmentioning
confidence: 72%
“…The highest iron content was found in SA-treated plants. Increased Fe concentration resulting from SA application was also reported in Arachis hypogaea [Kong et al, 2014]. The lowest Fe level was detected in the leaves of plants watered with CaCl 2 .…”
Section: Resultsmentioning
confidence: 72%
“…In the present study, SNP treatment increased not only the morphological parameters, but also some other physiological parameters, i.e., chlorophyll content and net photosynthesis rate (results not shown) as compared to control irrespective of concentrations of SNP. NO has also shown to have improved the leaf size and chlorophyll content in peanut plants (Arachis hypogaea L.) (Kong et al, 2014). Here, SNP promoted Fe uptake, translocation and activation; modulated the balance of mineral elements; and protected Fe deficiency induced oxidative stress in peanut plants (Kong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…NO has also shown to have improved the leaf size and chlorophyll content in peanut plants (Arachis hypogaea L.) (Kong et al, 2014). Here, SNP promoted Fe uptake, translocation and activation; modulated the balance of mineral elements; and protected Fe deficiency induced oxidative stress in peanut plants (Kong et al, 2014). Zhang et al (2012) showed that SNP application improved net photosynthesis and thereby increased the yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations